Retrospective analysis of the national impact of industrial action by English junior doctors in 2016 - Furnivall,D; Bottle,R; Aylin,P (BMJ Open, 2018)
Objectives: To examine the impacts of the four episodes of industrial action by English junior doctors in early 2016.Design: Descriptive retrospective study of admitted patient care, accident and emergency (A&E) and outpatient activity in English hospitals.Setting: All hospitals across England.Participants: All patients who attended A&E or outpatient appointments, or those who were admitted to hospital during the three week period surrounding each of the four strikes (January 12th, February 10th, March 9th-10th and April 26th-27th, excluding weekends.)Main outcome measures: Raw numbers and percentage changes of outpatient appointments and cancellations, A&E visits, admitted patients and all in-hospital mortality on strike days compared with patient activity on the same weekday in the weeks before and after the strikes.Results: There were 3.4 million admissions, 27 million outpatient appointments and 3.4 million A&E attendances over the four 3-week periods analysed. Across the four strike days, there were 31,651 fewer admissions (-9.1%), 23,895 fewer A&E attendances (-6.8%) and 173,462 fewer outpatient appointments (-6.0%) than expected. Additionally, 101,109 more outpatient appointments were cancelled by hospitals than expected (+52%). The April 26th-27th strike, where emergency services were also affected, showed the largest impacts on regular service. Mortality did not measurably increase on strike days. Regional analysis showed that services in the Yorkshire and the Humber region were disproportionately more affected by the industrial action. Conclusions: Industrial action by junior doctors during early 2016 caused a significant impact on the provision of healthcare provided by English hospitals. We also observed regional variations in how these strikes affected providers.